M. Zen Gomo dalam Gerakan Anti Korupsi pada Dekade I Reformasi di Sumatera Barat - Rizki Ilahi; Mestika Zed; Erniwati Erniwati (PAMA Aksara, 2019)
This is a study thematic biographer who discusses about M. Zen Gomo during join in the world of politics. The focused study is described and analyze the act of he did in motion anti-corruption in the reform. The purpose of this research gives descriptions of political activity M. Zen Gomo and place in movement anti-corruption in West Sumatra. The results of the study are that M. Zen Gomo joins politics since the end of the new order and the establishment of a national mandate party. While in politics and was a member of the council, he often faced with various problems that have contrary to principle to his refusal. Ranging from refuse to accept money in a local election in 2000, Refused money “unexpected” from the executive. The top of their actions is demanded that Sumbar 2002 budget to revised by his associates. The act of he did is also be supported by people who joined in Forum Peduli Sumatera Barat (FPSB), So that in 2004, some 43 council members West Sumatra suspect in the corruption case.